Federating diamond OA in Europe and beyond: the European Diamond Capacity Hub (EDCH) - Pierre Mounier; Johan Rooryck (Insights: The UKSG Journal)
This case study presents the context, governance and operations of the European Diamond Capacity Hub (EDCH) launched in January 2025. The EDCH will coordinate diamond open access (OA) capacity centres in Europe and consolidate and align the diamond OA organizations that provide services and tools to diamond OA outputs in Europe. In this way, it will provide the backbone for a scholarly communication infrastructure that is owned and operated by the academic community without charges for authors and readers.